Synthesis of meso-tetrasubstituted porphyrins, containing phosphoryl and azophenyl group - Ya. F. Al Ansari; V. E. Baulin; E. V. Savinkina; A. Yu. Tsivadze (Тонкие химические технологии, 2008)
New meso-tetrasubstituted porphyrins of interest as heterotopic ligands were synthesized. Substances are investigated by methods of electronic and IR-spectroscopy, МALDI-TOF mass-spectrometry, 1 H NMR spectroscopy and elemental analysis